Sports Medicine and Physical Fitness - Thomas, Ewan; Chulvi-Medrano, Ivan; Padua, Elvira (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Sports Medicine and Physical Fitness has been a successful Special Issue, which addressed novel topics in any subject related to sports medicine, physical fitness, and human movement. The article collection was able to positively evaluate three systematic reviews, nineteen original articles, and one brief report. These encompassed a broad range of topics ranging from accident kinematics, soccer monitoring, children's physical evaluation, adapted physical activity, physical evaluation for people with intellectual disabilities, performance analysis in rowers, ultramarathon racers, karateka's, rugby players, volleyball and basketball players, and cross-fit athletes, and also aspects related to biomechanics, fatigue and injury prevention in racing motorcycle riders, gymnasts, and cyclists.These scientific contributions within the field of Sports Medicine and Physical Fitness broaden the understanding of specific aspects of each analyzed discipline.It has been a pleasure for the Editorial Team to have served the International Journal Of Environmental Research and Public Health.